2016
DOI: 10.1136/bjophthalmol-2016-308764
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of automated vessel density measurements using optical coherence tomography angiography

Abstract: Commercial automated vessel density measurements using OCT-A showed excellent repeatability in healthy individuals. Although repeatability will also need to be established in the setting of disease, the level of reproducibility should be useful for assessing the significance of differences in capillary density over time or under different conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
130
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 26 publications
7
130
2
5
Order By: Relevance
“…Overall, we observed that the repeatability of vessel density measurements was higher for the superficial plexus than the deep plexus, similar to previous work,21 and is likely the result of higher resolution of the superficial plexus compared with the deep plexus on the instrument used for this study. We also noted the presence of significant variation in vessel density in our study population, which was comparable to that reported previously, although our study included a group of patients at older age compared with previous studies 23.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, we observed that the repeatability of vessel density measurements was higher for the superficial plexus than the deep plexus, similar to previous work,21 and is likely the result of higher resolution of the superficial plexus compared with the deep plexus on the instrument used for this study. We also noted the presence of significant variation in vessel density in our study population, which was comparable to that reported previously, although our study included a group of patients at older age compared with previous studies 23.…”
Section: Discussionsupporting
confidence: 88%
“…Macular quantitative parameters vary across different instruments and techniques (i.e., manual versus automatic assessment); however, several studies demonstrated that they have a good inter-and intraoperator reliability in case of same machine, acquisition and postprocessing protocols. [7][8][9]11,12,23 Measurement at the superficial plexus is highly reliable, while manual demarcation at the deep plexus may be not easy due to less definite contours.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that these parameters have high intraand interoperator reproducibility both in eyes with and without retinal diseases, for the same scan type and for the same machine. [7][8][9][10][11][12][13] In a study by Dong and coworkers, 14 a good agreement between 3 3 3-and 6 3 6-mm angiocubes was found for choriocapillary vessel density and for FAZ area at all retina vasculatures; conversely, reliability for retinal vessel density was weak. However, scan interchangeability has been only tested for small angiocubes and it remains uncertain for wider size scans (e.g., 12 3 12 mm).…”
mentioning
confidence: 99%
“…The image information signal is proportional to the blood flux and can be used to reflect the microcirculation. Split-spectrum amplitude decorrelation angiography algorithm has the advantage of reducing the interference signals and eye motions and is used to measure the avascular zone and superficial retinal vessel density in the macular zone with higher reliability [10, 11]. However, the reliability of vessel density measurement in the peripapillary retina is not clear.…”
Section: Introductionmentioning
confidence: 99%